Pengaruh City Branding terhadap City Image Serta Dampaknya pada Tourist Loyalty - Terra Saptina Maulani (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
To develop the economy and empower the community, one of the activities in developing the regional economy besides the industrial sector is the tourism sector. Tourism has a strategic role in creating jobs and generating foreign exchange and regional income. To restore the economy, there is a policy of 5 (five) pillars of economic, social, and cultural recovery, one of which is to increase marketing by strengthening the image of tourism. To improve the image of Bandung City tourism through a City Branding strategy to be more competitive and able to compete with other cities as a tourist destination. City Branding is not just a logo, symbol, or slogan but rather the delivery of a promise of an impressive trip so that it can make tourists loyal. Loyal tourists may want to make repeat visits and recommend to others. This research was done in Bandung City as the research object. . The data analysis method used in this study is quantitative, for testing the hypothesis using path analysis. The results of this study, show that City Branding influenced Tourist Loyalty through City Image by 26.7%.